Weaponized social media - Gordon, Sherri Mabry (Critical thinking about digital media., 2019)
Explains how social media is used for malicious intent, and answers key questions about the causes and consequences a weaponized social media presence. Highlights key examples of weaponized social media trends, and provides strategies for recognizing and combating social media hostility. Includes color photographs, chapter notes, a glossary, sources for further information, and an index.